1987
DOI: 10.3382/ps.0660705
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell Quality as Influenced by Sodium Bicarbonate, Calcium Source, and Photoperiod

Abstract: The effects of Ca source (limestone or a mixture of one-third limestone and two-thirds oyster shell), NaHCO3 (0 or .5%) and feeding photoperiod (16 or 24 hr) were studied in a 16-week experiment involving 240 Hy-Line W-36 Leghorn hens, 25 weeks of age. Neither egg production (percent hen-day and egg mass, kg egg/bird per 16 weeks) nor feed conversion ratio (kg feed per kg egg) were significantly (P greater than .05) affected by dietary treatment or photoperiod. However, extending the photoperiod to 24 hr signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 19 publications
1
9
1
Order By: Relevance
“…In contrast to our findings, former studies concerning OSM supplementation showed beneficial effects on eggshell breakage strength (Watkins et al, 1977;Brister et al, 1981;Makled & Charles, 1987;Proudfoot & Hulan, 1987;Guinotte & Nys, 1991;Grizzle et al, 1992;Ahmad & Balander, 2004). The results of the present study further support some recent investigations by Lichovnikova (2007) and Safaa et al (2008) who observed that oyster shell is less soluble than fine or coarse limestone, contradicting conventional theories of higher digestibility and retention associated with oyster shell by some researchers (Scott et al, 1971;Roland, 1988).…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…In contrast to our findings, former studies concerning OSM supplementation showed beneficial effects on eggshell breakage strength (Watkins et al, 1977;Brister et al, 1981;Makled & Charles, 1987;Proudfoot & Hulan, 1987;Guinotte & Nys, 1991;Grizzle et al, 1992;Ahmad & Balander, 2004). The results of the present study further support some recent investigations by Lichovnikova (2007) and Safaa et al (2008) who observed that oyster shell is less soluble than fine or coarse limestone, contradicting conventional theories of higher digestibility and retention associated with oyster shell by some researchers (Scott et al, 1971;Roland, 1988).…”
Section: Resultscontrasting
confidence: 56%
“…Some previous scientific publications also confirmed that laying hens did not benefit from either MBM (Oruseibio, 1995;Bozkurt et al, 2004) or OSM (Brister et al, 1981;Makled & Charles, 1987;Grizzle et al, 1992;De Faria et al, 2000;Safaa et al, 2008) supplementation of the diet.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Alteration in nutrient partitioning (Stepchenko et al, 1991;Parks, 1998) could be associated with increased egg production in hens Supplemented with humate. Makled and Charles (1987) reported that 0.5% NaHCO,, …”
Section: Resultsmentioning
confidence: 98%
“…by Roberts (2004), Franco-Jimenez et al (2007, and Oguntunji and Alabi (2010). Poorer egg shell quality in hens under heat stress was shown to be the result of hyperventilation and a lack of bicarbonate ions (Lorcher and Hodges, 1969;Makled and Charles, 1987). The highest specific gravity exhibited the eggs from young laying hens collected in the afternoon at 20°C (1.128) and the lowest the eggs laid in the afternoon by old broiler breeders (1.050); this four-way interaction proved to be significant (P = 0.050).…”
Section: Resultsmentioning
confidence: 86%